2023
DOI: 10.33012/navi.618
|View full text |Cite
|
Sign up to set email alerts
|

RFI Mapped by Spaceborne GNSS-R Data

Clara Chew,
T. Maximillian Roberts,,
Steve Lowe

Abstract: Global navigation satellite system (GNSS) signals, such as those transmitted by global positioning system (GPS) satellites, are used by both military and civilian users for navigation, positioning, and scientific purposes. Although signal transmission in GNSS bands by unauthorized persons is restricted, radio frequency interference (RFI) in the GNSS wavelengths can occur, either intentionally or unintentionally, which can limit or prevent the use of GNSS signals for their intended purpose. Often seen in confli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Different from broad L-band radio frequency interference (RFI) seen from space [11,12], the jamming on GNSS receivers is an intentional RFI, often concentrated in a narrow band targeted to a specific transmission frequency such as GPS [13]. These jamming or RFI signals must be flagged and removed in order to produce useful science data in GNSS-reflectometry (GNSS-R) observations [14][15][16][17]. Although GNSS-RO is largely based on phase measurements, the RO tracking can be adversely impacted by weak GNSS signals or signal-to-noise ratio (SNR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different from broad L-band radio frequency interference (RFI) seen from space [11,12], the jamming on GNSS receivers is an intentional RFI, often concentrated in a narrow band targeted to a specific transmission frequency such as GPS [13]. These jamming or RFI signals must be flagged and removed in order to produce useful science data in GNSS-reflectometry (GNSS-R) observations [14][15][16][17]. Although GNSS-RO is largely based on phase measurements, the RO tracking can be adversely impacted by weak GNSS signals or signal-to-noise ratio (SNR).…”
Section: Introductionmentioning
confidence: 99%
“…For slowly varying high power sources, the algorithm might have some challenges to distinguish them from other natural variabilities. Furthermore, studying the GNSS-R delay doppler map (DDM) measurement noise, Chew et al [17] obtained GNSS RFI maps from 2017 to 2022 and found the approximate locations of regional hot spots in the subtropical latitudes over land. The technique can be used to track and evaluate jamming sources at a relatively high revisit rate from an 8-SmallSat constellation.…”
Section: Introductionmentioning
confidence: 99%